F34 Game of dice task performance in premanifest huntington's disease subjects. (September 2018) - Migliore, Simone; D'Aurizio, Giulia; Maffi, Sabrina; Curcio, Giuseppe; Squitieri, Ferdinando
Abstract : Background: Huntington's Disease (HD) cognitive dysfunction may start before unequivocal motor signs become apparent. Main early cognitive abnormal domains may include deficits in psychomotor speed, negative emotion recognition, executive functioning and decision making. Game of Dice Task (GDT) activates various prefrontal cortex areas (PFC), i.e. dorsolateral PFC (DLPFC), that is a region showing a reduced activation in pre-manifest HD (pre-HD) stage. Aim: Our study aimed at investigating the decision making processing in pre-HD subjects, by means of GDT. Methods: We enrolled 28 preHD subjects (i.e. Total Motor Score ranging between 1 and 9 and DCL<4) and 21 healthy controls (HC). As dependent variables, several GDT outcomes have been taken into consideration. Results: The preHD group showed longer decision and feedback times with respect to HC in both disadvantageous (respectively p=0, 009 and p<0, 0001) and advantageous (respectively p=0, 01 and p=0, 006) choices. With respect to number of disadvantageous and advantageous choices, preHD group showed a greater amount of 'safe' strategies (p=0, 01) than HC group. Conclusions: PreHD subjects look more cautious in providing the answers to GDT than the HC cohort. Furthermore, they need a time to process a feedback from the previous trial longer than HC subjects. This explains their slowdown in providing the answer. Accordingly, the preHD group showed an increased carefulness, preferring 'safe' options. This could depict a typical profile of preHD behavior in risky decision-making.